56‐2: Optical Touch Screen Integrated With Fingerprint Recognition. Issue 1 (2nd June 2017) - Ma, Ping; Cao, Wensheng; Zheng, Shuyu; Cui, Xuecheng; Guo, Lindong; zheng, Jun; Ye, Zhicheng
Abstract : An optical touch panel integrated with fingerprint recognition function has been proposed and confirmed. Through tactical design with slanted grating and appropriate pitch, efficient coupling of waveguide mode for touch sensing and sufficient non‐overlapping area for fingerprint detecting were obtained simultaneously, meaning great potential for intelligent touch devices.